Learning to find food: evidence for embryonic sensitization and juvenile social learning in a salamander. (August 2018) - Crane, Adam L.; Helton, Emilee J.; Ferrari, Maud C.O.; Mathis, Alicia
Abstract : For many species, learning is an essential mechanism for dealing with the environment correctly and efficiently. Animals that quickly learn important information, and learn at a young age, can gain a competitive advantage in exploiting resources. Moreover, animals that learn indirectly through social observations can avoid the fitness costs of directly learning about potential dangers. Here we tested such learning capabilities in ringed salamanders, Ambystoma annulatum, a species where adults are primarily solitary and do not provide parental care. Adults lay eggs in ponds where embryos have the opportunity to learn from chemical cues in their environment before hatching, whereupon the high density of larvae provides an opportunity to learn from social information. In this study, we found that these salamanders can learn an attraction to novel food stimuli as embryos and that naïve observer larvae can learn from conspecifics that show attraction to stimuli. Embryonic exposure to a novel food stimulus (shrimp odour) caused attraction to that stimulus posthatching, and this response appeared to be generalized to another potential prey stimulus (mussel odour) but not to a novel plant stimulus. In a test of social learning, only observers that were paired with models corralled near a novel food stimulus were subsequently attracted to the stimulus. This study is the first to report embryonic learning of food or social learning by salamanders, providing more evidence for generalized learning by embryos and social learning by species lacking more complex social behaviours. Highlights: Embryonic exposure to a novel food stimulus caused posthatching attraction. Responses learned as embryos were also shown towards a similar stimulus as larvae. Larvae also learned attraction to a stimulus after observing a conspecific. Social learning can occur in species lacking complex social behaviour.